PENERAPAN PRINSIP TANGGUNG JAWAB MUTLAK (STRICT LIABILITY) TERHADAP KERUGIAN AKIBAT IKLAN MENYESATKAN - Gunawan Widjaja; Renaldi Immanuel Panggabean (ADISAM PUBLISHER, 2024)
One of the company's responsibilities is to provide accurate, transparent and honest information about its products. However, in reality, there are many misleading advertisements that can have many detrimental effects on consumers. One strategy that is considered useful to provide consumers with protection from business actors is the principle of responsibility without fault (absolute responsibility). The problems in this research are: 1) How is the application of the principle of strict liability for losses due to misleading advertising 2) How is the form of legal settlement in the event of losses due to misleading advertising. The method used in the research is normative legal research. Data processing is done with a qualitative juridical approach. The results of the research show: 1) If it is related to the principle of strict liability, the business actor must be directly responsible for the company's actions that cause harm to consumers 2) Legal settlement in the event of losses due to misleading advertising can be done in 2 ways, namely Non- litigation and Litigation.